Formulations for chemical mechanical polishing pads with high planarization efficiency and CMP pads made therewith
Patent Information
- Application Number
- JP2022006582
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-01-21
- Filing Date
- 2022-01-19
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-01-19
AI Technical Summary
Existing CMP polishing pads face a compromise between planarization efficiency and defectivity, with higher efficiency leading to increased defects, and current formulations fail to provide an acceptable removal rate and uniformity.
A CMP polishing pad formulation using a liquid aromatic isocyanate component with short-chain polyols and aromatic diamines, combined in a specific stoichiometric ratio, to create a porous polyurethane layer with controlled hardness and porosity, enhancing planarization efficiency while reducing defects.
The new formulation achieves improved planarization efficiency with reduced defectivity and maintains an attractive removal rate, outperforming conventional pads in both efficiency and uniformity.
Abstract
Description
Technical Field
[0001] The present invention relates to a chemical mechanical planarization (CMP) polishing pad and a method for manufacturing the same. More specifically, the present invention relates to a CMP polishing pad that is a polyurethane reaction product of a two-component reaction mixture containing a liquid aromatic diisocyanate component and a liquid polyol component (including a monoalkylene diol, such as ethylene glycol) and a liquid aromatic diamine curing agent.
Background Art
[0002] In the CMP process, the polishing pad is combined with a polishing solution such as an abrasive-containing polishing slurry and / or a reactive liquid without abrasive grains to remove excess material in a manner that flattens or maintains the flatness of a semiconductor, optical or magnetic substrate. There is a continuing need for a CMP polishing pad that enhances the layer uniformity or planarization performance in combination with an acceptable removal rate. However, in the industry, there remains a compromise in performance between planarization efficiency (PE) and defectiveness, with more defects as the PE increases. Known CMP polishing pads are formed from a reaction mixture containing an aromatic diamine as a curing agent. The higher the concentration of the aromatic diamine, the faster the reaction time and the better the mechanical properties such as high tensile strength and high tensile modulus. However, such CMP polishing pads with high tensile modulus and hardness can provide good planarization efficiency, but there remains a compromise in the increase of defects generated during polishing.
[0003] U.S. Patent Application Publication No. 2009 / 0062414 (A1) by Huang et al. discloses a CMP polishing pad produced by foaming an aliphatic isocyanate containing a urethane prepolymer with an inert gas in the presence of a polysiloxane-polyalkylene oxide surfactant and curing the foam with a curing agent containing an aromatic diamine and a triol. The obtained CMP polishing pad has improved damping performance and a density of 0.6 to 1.0 g / cm 3 . However, the obtained polishing pad cannot provide an acceptable removal rate during polishing.
[0004] Barton et al.'s U.S. Patent Application Publication No. 20180148537 discloses a CMP polishing pad prepared by reacting a liquid aromatic isocyanate compound with a liquid polyol using one or more polyamine or diamine curing agents. However, this reference fails to recognize the importance of blending a short-chain polyol with a diamine in relation to its effect on the planarization efficiency of the resulting polishing pad.
[0005] The inventors have strived to solve the problem of providing a more flexible compounding method for producing a chemical-mechanical polishing layer or pad that is useful for polishing dielectric and silicon oxide substrates and maintains good removal speed and planarization efficiency (PE) performance without an undesirable increase in defects and hardness. [Overview of the Initiative]
[0006] 1. According to the present invention, a chemical mechanical polishing (CMP polishing) pad for polishing a substrate selected from at least one of a magnetic substrate, an optical substrate, and a semiconductor substrate comprises a polishing layer adapted for polishing the substrate, the polishing layer is (i) A liquid aromatic isocyanate component comprising one or more aromatic diisocyanates or linear aromatic isocyanate-terminated urethane prepolymers, wherein the prepolymer has an unreacted isocyanate (NCO) concentration of 20 to 40% by weight, or preferably 18 to 34% by weight, relative to the total solids weight of the liquid aromatic isocyanate component; preferably, a liquid aromatic isocyanate component comprising a linear methylenediphenyl diisocyanate (MDI) prepolymer, (ii) A liquid polyol component, a) One or more polymer polyols (e.g., polytetramethylene glycol (PTMEG), polypropylene glycol (PPG)), polyols having 5 to 7 hydroxyl groups (e.g., hexafunctional polyols or mixtures thereof), b) 12 to 40% by weight, or preferably 15 to 25% by weight, of the total weight of the liquid polyol component, of a short-chain bifunctional polyol having 1 or more carbon atoms (e.g., ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol and mixtures thereof; preferably ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol and triethylene glycol), A liquid polyol component comprising a liquid aromatic diamine that is liquid under ambient conditions [e.g., dimethylthiotoluenediamine, diethyltoluenediamine; tert-butyltoluenediamine (e.g., 5-tert-butyl-2,4- or 3-tert-butyl-2,6-toluenediamine); chlorotoluenediamine; and N,N'-dialkylaminodiphenylmethane and mixtures thereof; preferably, any liquid aromatic diamine selected from chlorotoluenediamine or dimethylthiotoluenediamine, diethyltoluenediamine (DETDA) and N,N'-dialkylaminodiphenylmethane, and a curing agent mixture thereof, and The polyurethane reaction product comprises a substantially water-free and organic solvent-free two-component reaction mixture containing the following: Here, the molar ratio of liquid aromatic diamine to the total number of moles of short-chain bifunctional polyol and liquid aromatic diamine is in the range of 15:85 to 40:60, or preferably 23:77 to 35:65; further, the reaction mixture contains 48 to 68% by weight, or preferably 58 to 63% by weight, of hard segment material relative to the total weight of the reaction mixture; further, the CMP polished layer has a hardness in the range of 50 Shore A (15 sec) to 68 Shore D (15 sec), or preferably 55 Shore A (15 sec) to 50 Shore D (15 sec), and a density of 0.45 to 0.9 g / mL, or preferably 0.60 to 0.85 g / mL; and preferably, further, the CMP polished layer does not contain trace elements other than those formed by gas, water, or CO2-amine adducts.
[0007] 2. According to the present invention, in a reaction mixture that does not contain an organic solvent for forming the chemical mechanical polishing (CMP polishing) layer described in item 1 above, (i) The liquid aromatic isocyanate component is selected from methylenediphenyl diisocyanate (MDI); toluene diisocyanate (TDI); naphthalene diisocyanate (NDI); paraphenylenedi diisocyanate (PPDI); or o-toluidine diisocyanate (TODI); modified diphenylmethane diisocyanate (e.g., carbodiimide-modified diphenylmethane diisocyanate, allophanate-modified diphenylmethane diisocyanate, biuret-modified diphenylmethane diisocyanate); a linear isocyanate-terminated urethane prepolymer having a hard segment weight fraction of 84-100% by weight, preferably 90-100% by weight, more preferably MDI or a linear isocyanate-terminated urethane prepolymer of MDI or an MDI dimer, It comprises one or more isocyanate extenders selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol, and mixtures thereof.
[0008] 3. According to the present invention, in a reaction mixture that does not contain an organic solvent for forming a chemical mechanical polishing (CMP polishing) layer as described in either item 1 or 2 above, ii)b) The curing agent mixture comprises one or more short-chain bifunctional polyols having 2 to 9 carbon atoms and a liquid aromatic diamine, The liquid aromatic diamine is selected from dimethylthiotoluenediamine, a mixture of isomers of 2,4-diamino-3,5-dimethylthiotoluene; 3,5-dimethylthio-2,4-toluenediamine; diethyltoluenediamine; tert-butyltoluenediamine (e.g., 5-tert-butyl-2,4- or 3-tert-butyl-2,6-toluenediamine); chlorotoluenediamine; and N,N'-dialkylaminodiphenylmethane and mixtures thereof; preferably, selected from chlorotoluenediamine or dimethylthiotoluenediamine, a mixture of isomers of the isomers 2,4-diamino-3,5-dimethylthiotoluene and 3,5-dimethylthio-2,4-toluenediamine, diethyltoluenediamine (DETDA), and N,N'-dialkylaminodiphenylmethane.
[0009] 4. According to the present invention, in a reaction mixture that does not contain an organic solvent for forming a chemical mechanical polishing (CMP polishing) layer as described in any one of items 1, 2, or 3 above, the stoichiometric ratio of the sum of the total moles of amine (NH2) groups and the total moles of hydroxyl (OH) groups in the reaction mixture to the total number of moles of unreacted isocyanate (NCO) groups in the reaction mixture is in the range of 0.85:1.0 to 1.15:1.0, or preferably 0.9:1.0 to 1.1:1.0.
[0010] 5. According to the chemical-mechanical polishing pad of the present invention described in any one of items 1, 2, 3, or 4 above, the polishing pad or polishing layer has a density of 0.45 to 0.9 g / mL, or preferably 0.60 to 0.85 g / mL, which is generated from c) water or CO2-amine adduct in ii) a liquid polyol component.
[0011] 6. According to the chemical-mechanical polishing pad of the present invention as described in any one of items 1, 2, 3, 4, or 5 above, the polishing pad further includes a sub-pad or backing layer, such as a polymer-impregnated nonwoven fabric or polymer sheet, on the bottom side of the polishing layer, such that the polishing layer forms the upper part of the polishing pad.
[0012] 7. In another embodiment, the present invention provides a method for manufacturing a chemical-mechanical (CMP) polishing pad having a polishing layer adapted for polishing substrates. The method is, A step of providing a two-component reaction reaction according to any one of the above items 1, 2, 3, 4, 5, or 6, The process involves adding, to the liquid polyol component ii), a sufficient amount of, for example, c) water or a CO2-amine adduct (e.g., CO2-alkanolamine) to generate the density of the CMP polishing pad or layer, such as, for example, 250 to 3000 ppm, or preferably 500 to 2000 ppm of water, or 0.05 to 2% by weight, or preferably 0.1 to 1.5% by weight, relative to the total weight of the two-component reaction mixture. A step of mixing a liquid aromatic isocyanate component (i) and a liquid polyol component (ii) using, for example, a static mixer or a collision mixer, The process involves applying the reaction mixture as one component to the surface of an open mold, preferably to an open mold surface having a male mold shape that forms a female mold groove pattern on the upper surface of a CMP polishing pad or layer. A method for producing a chemical mechanical (CMP) polishing pad is provided, comprising the steps of curing a reaction mixture at an ambient temperature of ~130°C to form a molded polyurethane reaction product, for example, first curing at an ambient temperature of ~130°C for 1 to 30 minutes, preferably 30 seconds to 5 minutes; removing the polyurethane reaction product from the mold; and then performing a final curing at a temperature of 60 to 130°C for 1 minute to 18 hours, preferably 5 minutes to 60 minutes, to form a CMP polishing pad or layer.
[0013] 8. The step of forming a polishing pad by the method of the present invention described in item 7 above further includes the step of laminating or spraying a sub-pad layer, such as a polymer-impregnated nonwoven fabric or a porous or non-porous polymer sheet, to the bottom side of the polishing layer so that the polishing layer forms the upper surface of the polishing pad.
[0014] 9. The surface of the CMP polishing pad is formed directly in the mold by the method of the present invention described in either item 7 or 8 above.
[0015] 10. The method of the present invention described in any one of items 7, 8, or 9 above, comprising the step of applying the reaction mixture as one component, the step of topcoating a mold, subsequently curing to form a polyurethane reaction product, removing the polyurethane reaction product from the mold, and then punching or cutting around the polyurethane reaction product to a desired diameter for a CMP polishing pad.
[0016] 11. In yet another aspect, the present invention provides a substrate polishing method comprising the steps of: providing a substrate selected from at least one of a magnetic substrate, an optical substrate, and a semiconductor substrate (e.g., a dielectric or silicon oxide-containing substrate); providing a chemical-mechanical (CMP) polishing pad as described in any one of items 1 to 6 above; generating dynamic contact between the polishing surface of the polishing layer of the CMP polishing pad and the substrate to polish the surface of the substrate; and conditioning the polishing surface of the polishing pad with an abrasive conditioner.
[0017] Unless otherwise noted, temperature and pressure conditions are ambient temperature and standard pressure. All listed ranges include boundary values and are combinable.
[0018] Unless otherwise noted, any term containing parentheses means either the entire term without parentheses, the term without parentheses, or any combination of these options. Therefore, the term "(poly)isocyanate" refers to isocyanate, polyisocyanate, or a mixture thereof.
[0019] For the purposes of this specification, the reaction mixture is expressed in weight percent unless otherwise stated.
[0020] All ranges include boundary values and are combinable. For example, the term "range of 50 to 3000 cP, or 100 cP or more" encompasses 50 to 100 cP, 50 to 3000 cP, and 100 to 3000 cP, respectively.
[0021] As used herein, the term "ASTM" refers to publications by ASTM International in West Conshohocken, Pennsylvania.
[0022] As used herein, the term "average number of isocyanate groups" means the weighted average of the number of isocyanate groups in a mixture of aromatic isocyanate compounds. For example, a 50:50 weight % mixture of MDI (2 NCO groups) and the isocyanurate of MDI (which is considered to have 3 NCO groups) has an average of 2.5 isocyanate groups.
[0023] As used herein, the term "hard segment" of a polyurethane reaction product or of a raw material derived from (ii) a liquid polyol component and (i) a liquid aromatic isocyanate component refers to the portion of a specified reaction mixture that includes any diol, glycol, diglycol, diamine or triamine, diisocyanate, triisocyanate or reaction product thereof. Thus, "hard segment" excludes polyethers, or polyglycols (e.g., polyethylene glycol or polypropylene glycol), or polyoxyethylene having three or more ether groups.
[0024] As used herein, the term "trace elements other than those formed by a gas, water, or CO2 - amine adduct" means trace elements selected from hollow core polymer materials, such as polymer microspheres, liquid - filled hollow core polymer materials, such as fluid - filled polymer microspheres, and fillers, such as boron nitride. Pores formed in a CMP polishing layer by a gas, or a blowing agent that only forms a gas, such as a CO2 - amine adduct, are not considered trace elements.
[0025] As used herein, the term "polyisocyanate" means any isocyanate - group - containing molecule that contains two or more isocyanate groups.
[0026] As used herein, the term "polyurethane" refers to a polymerization product derived from a bifunctional or polyfunctional isocyanate, such as a polyether urea, polyisocyanurate, polyurethane, polyurea, polyurethane urea, its copolymers and its mixtures.
[0027] As used herein, the term “reaction mixture” includes any non-reactive additives, such as trace elements and any additives that reduce the hardness of the polyurethane reaction product in the CMP polishing pad according to ASTM D2240-15 (2015).
[0028] As used herein, the term “stoichiometry” of a reaction mixture refers to the ratio of the molar equivalents of (free OH + free NH2 groups) to the free NCO groups in the reaction mixture.
[0029] As used herein, the term "SG," i.e., "specific gravity," refers to the weight / volume ratio of a rectangular cut piece from a polishing pad or layer according to the present invention.
[0030] As used herein, the term “Shore D hardness” refers to the 15-second hardness of a given CMP abrasive measured according to ASTM D2240-15(2015),''Standard Test Method for Rubber Property-Durometer Hardness,''. Hardness was measured using a Rex Hybrid hardness tester (Rex Gauge Company, Inc., Buffalo Grove, Illinois) equipped with a D probe. Six samples were stacked and rotated for each hardness measurement, and each pad tested was conditioned for 5 days at 23°C and 50 percent relative humidity using the method outlined in ASTM D2240-15(2015) before testing to improve the reproducibility of the hardness tests. In this invention, the Shore D hardness of the polyurethane reaction product of the abrasive layer or pad includes the Shore D hardness of the reactant, including any additives to improve hardness. The term “Shore A” hardness refers to the same 15-second hardness measurement using a larger A probe for softer materials.
[0031] As used herein, the term "solids" refers to any material remaining in the polyurethane reaction product of the present invention. Therefore, the solids include reactive liquids, non-volatile additives, and liquids that do not volatilize during curing. The solids exclude water and volatile solvents.
[0032] As used herein, unless otherwise stated, the term “substantially water-free” means that no water is added to a given composition, and no water is added to any material entering the composition. A “substantially water-free” reaction mixture may contain water present in the raw materials in the range of 50 to 2000 ppm, preferably 50 to 1000 ppm, or may contain reaction water produced in a condensation reaction, or vapor from ambient moisture in which the reaction mixture is being used.
[0033] As used herein, unless otherwise specified, the term “organic solvent-free” means that no organic solvent has been added to the composition, preferably the composition contains no organic solvent at all.
[0034] As used herein, unless otherwise specified, the term "viscosity" refers to the viscosity of a given undiluted (100%) material as measured at a given temperature using a rheometer set to a vibrating shear rate sweep of 0.1 to 100 rad / sec in a 50 mm parallel plate configuration with a 100 μm gap.
[0035] As used herein, unless otherwise specified, the term "weight %NCO" refers to the amount of unreacted or free isocyanate groups in a given isocyanate or isocyanate-terminated urethane prepolymer composition.
[0036] As used herein, the term "weight %" refers to weight percentage.
[0037] In this invention, the inventors have discovered that a CMP polishing pad made from a reaction mixture containing a short-chain bifunctional polyol having 1 to 2-9 carbon atoms in a liquid polyol component as part of a curing agent mixture provides a porous CMP polishing layer having a Shore D (15 sec) hardness of over 30, giving an attractive removal rate profile and enabling polishing with low defect content. In particular, reducing the content of liquid aromatic diamine and replacing this diamine portion with a short-chain diol results in a remarkable increase in planarization efficiency, despite a decrease in tensile properties and hardness. The increase in planarization efficiency (PE) accompanied by a decrease in tensile properties and hardness is remarkable.
[0038] The reaction mixture of the present invention may include an ultra-rapid curing composition in which (i) a liquid aromatic isocyanate component and (ii) a liquid polyol component can gel in a short gelation time of 15 seconds at 65°C. The reaction must be slow enough so that the reaction mixture can be mixed in a static or impact mixer. The only limitation on the gelation time is that the reaction mixture must react slowly enough so as not to clog the mixing head into which the reaction mixture is mixed and to properly fill the mold when the reaction mixture is applied to the mold surface.
[0039] The hard segment of the reaction mixture ensures good mechanical properties. The hard segment can constitute 56.25 to 68% by weight of the reaction mixture and can include portions of both the liquid polyol component and the liquid aromatic isocyanate component.
[0040] As part of the hard segment of the reaction mixture, (i) the liquid aromatic isocyanate component is preferably methylenediphenyl diisocyanate (MDI), which is less toxic than toluene diisocyanate (TDI). The liquid aromatic isocyanate component may include a linear isocyanate-terminated urethane prepolymer formed from short-chain diols such as glycols and diglycols, preferably monoethylene glycol (MEG), dipropylene glycol (DPG), or tripropylene glycol (TPG).
[0041] Preferably, the (i) liquid aromatic isocyanate component of the present invention contains a small amount of aliphatic isocyanate, up to 5% by weight, or more preferably up to 1% by weight, relative to the total weight of the liquid aromatic isocyanate.
[0042] The soft segment of the reaction mixture may contain, as a polymer polyol, (ii) a) 1 or more bifunctional polyether polyols in an amount of up to 88% by weight of the liquid polyol component. Preferred soft polyols are PTMEG and PPG. Available examples of PTMEG-containing polyols are: Terathane® 2900, 2000, 1800, 1400, 1000, 650 and 250 from Invista, Wichita, Kansas; Polymeg® 2900, 2000, 1000 and 650 from Lyndell Chemicals, Limerick, Pennsylvania; and PolyTHF® 650, 1000 and 2000 from BASF Corporation, Florham Park, New Jersey. Available examples of PPG-containing polyols include: Arcol® PPG-425, 725, 1000, 1025, 2000, 2025, 3025, and 4000 from Covestro in Pittsburgh, Pennsylvania; the Voranol®, Voralux®, and Specflex® product lines from Dow in Midland, Michigan; and Multranol®, Ultracel®, Desmophen®, or Acclaim® Polyol 12200, 8200, 6300, 4200, and 2200 from Covestro (Leverkusen, Germany), respectively.
[0043] The soft segment of the reaction mixture may contain, as a polymer polyol, one or more polyols having a polyether skeleton and 5 to 7, preferably 6, hydroxyl groups per molecule. Preferably, the soft segment of the reaction mixture contains, as a polymer polyol, a mixture of one or more polyols having a polyether skeleton and 5 to 7, preferably 6, hydroxyl groups per molecule and a bifunctional polyether polyol, more preferably a mixture in which polyols having a polyether skeleton and 5 to 7, preferably 6, hydroxyl groups constitute up to 20% by weight of the total liquid polyol component (ii).
[0044] Suitable polyols having a polyether skeleton and 5 to 7 hydroxyl groups per molecule are available as VORANOL® 202 polyol (Dow) having 5 hydroxyl groups, a number average molecular weight of 590, and a hydroxyl value of 475 mgKOH / g; MULTRANOL® 9185 polyol (Dow) having 6 hydroxyl groups, a number average molecular weight of 3,366, and a hydroxyl value of 100 mgKOH / g; or VORANOL® 4053 polyol (Dow) having an average of 6.9 hydroxyl groups, a number average molecular weight of 12,420, and a hydroxyl value of 31 mgKOH / g.
[0045] The stoichiometry of the reaction mixture of the present invention is in the range of (NH+OH):NCO 0.85:1.0 to 1.15:1.0. If the stoichiometry exceeds the upper limit, the polyurethane product will suffer a decrease in elongation at break. For the purposes of this specification, stoichiometry represents the molar ratio of amine or hydroxyl groups to isocyanate.
[0046] The curing agent mixture of the present invention is a liquid containing one or more liquid aromatic diamines and one or more short-chain bifunctional polyols having 2 to 9 carbon atoms. Suitable short-chain bifunctional polyols having 2 to 9 carbon atoms may be ethylene glycol, butanediol (BDO), dipropylene glycol (DPG), diethylene glycol (DEG), triethylene glycol (TEG), and mixtures thereof. However, the amount of short-chain bifunctional polyols having one or more short-chain bifunctional polyols having 2 to 9 carbon atoms in the curing agent mixture is in the range of at least 15 mol% of the curing agent mixture. If the amount of liquid aromatic diamine exceeds 85 mol%, the resulting CMP polishing layer or pad will be hard, but the desired improvement in PE and defect properties will not be achieved.
[0047] The hard segment of the reaction mixture of the present invention is in the range of more than 56.25% by weight of the total reaction mixture, preferably at least more than 60% by weight, in order to maintain appropriate tensile properties such as elastic modulus and appropriate hardness for use as a rigid top pad exhibiting high PE.
[0048] The liquid reaction mixture of the present invention makes it possible to provide CMP polishing pads by a method of spraying the reaction mixture into an open mold and curing the reaction mixture. The two-component polyurethane forming reaction mixture of the present invention is liquid and can be mixed in a static mixer or an impact mixer and sprayed to form CMP polishing pads.
[0049] The chemical-mechanical polishing pad of the present invention comprises a polishing layer which is a uniform dispersion of porous polyurethane. Homogeneity is important for achieving consistent polishing pad performance. Therefore, the reaction mixture of the present invention is selected so that the resulting pad morphology is stable and easily reproducible. For example, for consistent production, it is often important to control additives such as antioxidants and impurities such as water. Since water reacts with isocyanates to form gaseous carbon dioxide and generally weaker reaction products compared to polyurethane, the water concentration can affect the concentration of carbon dioxide bubbles that form pores in the polymer matrix and the overall uniformity of the polyurethane reaction product. In addition, accidental reactions of isocyanates with water tend to reduce the amount of isocyanate available for reaction with chain extenders, thereby changing the stoichiometric amount, including the crosslinking level (if an excess of isocyanate groups is present), and lowering the molecular weight of the resulting polymer. To reduce the variability of the effect of water on polyurethane, the water content in the raw materials is monitored and adjusted to a specific value of 0 ppm to 1000 ppm, preferably 50 ppm to 500 ppm.
[0050] Preferably, in order to maintain the stability of the pore structure in the reaction mixture and in the porous polyurethane constituting the CMP polishing layer or pad of the present invention, (ii) the liquid polyol component comprises a nonionic surfactant, preferably an organopolysiloxane-co-polyether surfactant, in an amount of up to 2.0% by weight, or preferably 0.1 to 1% by weight, relative to the total solids weight of the reaction mixture.
[0051] Preferably, (i) a catalyst can be used to improve the reactivity of the liquid polyol component with the liquid aromatic isocyanate component. Suitable catalysts include any catalyst known to those skilled in the art, such as oleic acid, azelaic acid, dibutyltin dilaurate, tin octoate, bismuth octoate, 1,8-diazabicyclo[5.4.0]undeca-7-ene (DBU), tertiary amine catalysts, such as Dabco™ TMR catalyst (Air Products, Allentown, Pennsylvania), triethylenediamine, such as DABCO™ 33LV catalyst (Air Products), and mixtures thereof.
[0052] The reaction mixture of the present invention is substantially water-free and does not contain any added organic solvents.
[0053] The specific gravity of the resulting CMP polishing pad is preferably in the range of 0.9 to 0.5. As porosity increases, the bulk properties of the CMP polishing pad decrease and the removal rate (RR) increases. However, in hard porous CMP polishing pads, planarization efficiency (PE) and defect properties are not expected to improve with increasing hardness or weight fraction of hard segment material.
[0054] Porosity is introduced to the pad by the spraying process, and the tensile modulus of the resulting pad is a function of both the intrinsic polymer tensile modulus and porosity, with increasing porosity acting to decrease the bulk modulus. Typical densities obtained on a two-component spray manufacturing platform range from 0.5 g / mL to 0.9 g / mL, more typically from 0.6 g / mL to 0.8 g / mL.
[0055] The density of the polishing pad is measured according to ASTM D1622-08 (2008). Density is the same as specific gravity.
[0056] The CMP polishing pad of the present invention is formed by a spray application method, which enables higher processing capacity and lower costs. Preferably, the target or substrate in the method of the present invention is a mold having a groove pattern into which the manufactured CMP polishing pad is directly incorporated.
[0057] The CMP polishing pad of the present invention is effective for polishing interlayer dielectrics (ILDs) and inorganic oxides. For the purposes of this specification, the removal rate is expressed as a removal rate in Å / min.
[0058] The chemical-mechanical polishing pad of the present invention may include simply a polishing layer of polyurethane reaction products, or a sub-pad or a polishing layer laminated on a sub-layer. In the case of the polishing pad or laminated pad of the present invention, the polishing layer of the polishing pad of the present invention is useful in both porous and non-porous (or unfilled) configurations.
[0059] Preferably, the CMP polishing layer used in the chemical-mechanical polishing pad of the present invention has an average thickness of 500 to 3750 microns (20 to 150 mils), more preferably 750 to 3150 microns (30 to 125 mils), even more preferably 1000 to 3000 microns (40 to 120 mils), and most preferably 1250 to 2500 microns (50 to 100 mils).
[0060] The chemical-mechanical polishing pad of the present invention optionally further comprises at least one additional layer in contact with the polishing layer. Preferably, the chemical-mechanical polishing pad optionally further comprises a compressible sub-pad or base layer bonded to the polishing layer. The compressible base layer preferably improves the fit of the polishing layer to the surface of the substrate to be polished.
[0061] The CMP polishing layer of the chemical mechanical polishing pad of the present invention has a polishing surface adapted for polishing substrates. Preferably, the polishing surface has a macrotexture selected from at least one of perforations and grooves. The perforations may extend partially from the polishing surface or throughout the entire thickness of the polishing layer.
[0062] Preferably, the grooves are positioned on the polishing surface such that at least one groove sweeps over the surface of the substrate being polished as the chemical-mechanical polishing pad rotates during polishing.
[0063] Preferably, the CMP polishing layer of the chemical mechanical polishing pad of the present invention has a polishing surface adapted for polishing substrates, the polishing surface having a macrotexture formed on its surface, including a groove pattern selected from curved grooves, linear grooves, perforations and combinations thereof. Preferably, the groove pattern includes a plurality of grooves. More preferably, the groove pattern is selected from groove designs selected from the group consisting of concentric grooves (which may be circular or helical), curved grooves, linear grooves, cross-hatch grooves (e.g., arranged as an XY grid across the pad surface), other regular designs (e.g., hexagons, triangles), tire tread patterns, radial irregular designs (e.g., fractal patterns) and combinations thereof. More preferably, the groove design is selected from the group consisting of random grooves, concentric grooves, helical grooves, cross-hatch grooves, XY grid grooves, hexagonal grooves, triangular grooves, fractal grooves and combinations thereof. The groove contour is preferably selected from a rectangle with flat side walls, or the groove cross-section may be V-shaped, U-shaped, serrated, or a combination thereof.
[0064] The method for manufacturing a CMP polishing pad according to the present invention allows for the formation of a macrotexture or groove pattern on the polishing surface of the chemical mechanical polishing pad, thereby promoting slurry flow and removing polishing debris from the pad-wafer interface. Such grooves may be formed on the polishing surface of the polishing pad from the shape of the mold surface, i.e., the mold has a female mold shape version of the macrotexture.
[0065] The chemical-mechanical polishing pad of the present invention can be used to polish substrates selected from at least one of magnetic substrates, optical substrates, and semiconductor substrates.
[0066] Preferably, the method for polishing a substrate according to the present invention includes the steps of: providing a substrate selected from at least one of a magnetic substrate, an optical substrate, and a semiconductor substrate (preferably a semiconductor substrate, such as a semiconductor wafer); providing a chemical-mechanical polishing pad according to the present invention; generating dynamic contact between the polishing surface of the polishing layer and the substrate to polish the surface of the substrate; and conditioning the polishing surface with an abrasive conditioner.
[0067] The process of conditioning the polishing pad includes bringing a conditioning disc into contact with the polishing surface, either during intermittent interruptions in the CMP process when polishing is paused ("ex situ"), or while the CMP process is in progress ("in situ"). The conditioning disc typically has a rough conditioning surface consisting of embedded diamond points that cut fine ridges into the pad surface, and the conditioning surface both wears and excavates the pad material, updating the polishing texture. Typically, the conditioning disc rotates in a fixed position relative to the rotation axis of the polishing pad, sweeping an annular conditioning area as the polishing pad rotates.
[0068] Examples: The present invention will now be described in detail by the following non-limiting examples. Unless otherwise stated, all temperatures are room temperature (21-23°C) and all pressures are atmospheric pressure (approximately 760 mmHg or 101 kPa).
[0069] Notwithstanding the other raw materials disclosed below, the following raw materials were used in the examples: Ethacure™ 300 curing agent: Dimethylthiotoluenediamine (DMTDA), aromatic diamine (Albemarle, Charlotte, North Carolina).
[0070] Voranol (trademark) V 5055 HH polyol: polyfunctional polyether polyol (OH equivalent 2000), functional groups = 6, number average molecular weight M = 12,000 NA propylene oxide polyol capped with high molecular weight ethylene oxide (The Dow Chemical Company, Midland, Michigan (Dow)).
[0071] MDI prepolymer: Linear isocyanate-terminated urethane prepolymer derived from MDI and low molecular weight dipropylene glycol (DPG) and tripropylene glycol (TPG), with an NCO content of approximately 23% by weight and an equivalent of 182. 100% by weight of this MDI prepolymer is treated as a hard segment.
[0072] Niax (trademark) L5345 surfactant: nonionic organosilicon surfactant (Momentive, Columbus, Ohio).
[0073] DABCO 33 LV: DABCO 33 LV (Air Products, Allentown, Pennsylvania), an amine catalyst made from diazobicyclononane (triethylenediamine), is a blend of 33% by weight triethylenediamine and 67% by weight dipropylene glycol.
[0074] Unilink® 4200 hardener: N,N'-dialkylamino-diphenylmethane (Dorf Ketal, Stafford, Texas)
[0075] PTMEG####: Poly(THF) or polytetramethylene glycol, produced via ring-opening polymerization of tetrahydrofuran (THF) and marketed as PolyTHF® polyol (BASF, Germany, Leverkusen). The number following PTMEG is the average molecular weight reported by the manufacturer. DPG: Dipropylene glycol BDO: 1,4-butanediol
[0076] PG: Monopropylene glycol (a product of Dow).
[0077] AOX-1: Benzofuranone compound, antioxidant (Milliken product Milliguard AOX-1).
[0078] INT1940: Fatty acid surfactant (Axel Plastics product Mold Wiz INT-1940 RTM). The characteristics of the CMP polishing pads were evaluated according to the following method.
[0079] All tensile properties were measured according to ASTM D412-06a, "Standard Test Methods for Vulcanized Rubber and Thermoplastic Elastomers - Tension." Samples were cut to dogbone C-type dimensions. Unless otherwise noted, five test pieces were measured, and the average value of all test pieces was reported for each sample.
[0080] Tensile elongation at fracture: This refers to the ratio of the length changed after fracture to the initial length of the test specimen, and is tested according to ASTM D412-06a(2006), "Standard Test Methods for Vulcanized Rubber and Thermoplastic Elastomers - Tension."
[0081] In all of the following examples, the two-component reaction mixtures shown were mixed and sprayed into an open mold using an impinging mixed air atomization system having two tanks (an isotank and a polytank) for supplying the mixture to the mixing system. The two tanks were set to a given material flow rate so that the relative amounts of each component could be immediately determined. The flow from the two tanks was started and stopped simultaneously. CMP polishing pads according to both the present invention and comparative examples were formed as follows.
[0082] Comparative Example 1: Flat plate and pad: In a mixing cup, 39 parts (97.50 g, 0.0513 equivalent mol) of propylene oxide polyol capped with ethylene oxide with a functional value of 6 and equivalent wt = 1900 (Dow's product Voranol® 5055HH) were combined with 1 part (2.50 g) of Niax® L 5345 surfactant, 15.47 parts (38.68 g, 0.3615 mol) of Ethacure® 300 liquid aromatic diamine, and 1.92 parts (4.80 g, 0.155 equivalent mol) of monoethylene glycol. To this degassed mixture, 42.608 parts (106.52 g, 0.5852 equivalent mol) of MDI prepolymer were added. The cup was then mixed in a vortex mixer for 30 seconds, then poured into a mold to form a plate, and cured at 100°C for 16 hours. The reaction mixture had a weight fraction of 60% hard segments, a stoichiometric ratio of 95% (0.95:1), and contained 15.47% liquid aromatic diamine. The molar ratio of liquid aromatic diamine to the total number of moles of diamine and polyol in the curing agent mixture was 70%. After curing, a plate with a density of 1.16 g / mL exhibited a tensile modulus of 579 MPa (84,000 psi), a tensile strength of 40.7 MPa (5,900 psi), and a tensile elongation at break of 175%.
[0083] The reaction mixture described above was sprayed onto an open mold using a two-component collision-type mixed air atomization system. The MDI prepolymer was loaded into an isotank, and simultaneously, 67.60 parts (47.32 pounds) of Voranol® 5055HH, 3.33 parts (2.33 pounds) of monoethylene glycol, 1.73 parts (1.21 pounds) of Niax® L5345, and 26.81 parts (18.77 pounds) of Ethacure® 300 were loaded into a polytank in the same proportions as used in the flattening process described above. The flow rates during spraying were 9.49 g / sec on the polyol side and 7.01 g / sec on the isotank side. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pads were cured in a 100°C oven for 15 minutes, then removed from the mold and cured in a 100°C oven for 16 hours. The resulting pads contained both radial and concentric grooves. The manufactured pads exhibited an average density of 0.762 g / mL, a bulk tensile modulus of 251.6 MPa (36,500 psi), a tensile strength of 15.2 MPa (2,200 psi), and a tensile elongation of 65%.
[0084] Example 2: Flat plate and pad In a mixing cup, 39.6 parts (99.0 g, 0.0521 equivalent mol) of propylene oxide polyol capped with ethylene oxide with a functional value of 6 and equivalent wt = 1900 (Dow's product Voranol® 5055HH) was combined with 1 part (2.50 g) of Niax® L5345 surfactant, 8.33 parts (20.82 g, 0.1946 equivalent mol) of Ethacure® 300, and 4.48 parts (11.20 g, 0.3613 equivalent mol) of monoethylene glycol. To this degassed mixture, 46.59 parts (116.48 g, 0.640 equivalent mol) of MDI prepolymer was added. The cup was then mixed in a vortex mixer for 20 seconds, then poured into a mold to form a plate, and cured at 100°C for 16 hours. The formulation is described as having a weight fraction of 60% hard segments, a stoichiometric ratio of 95%, and containing 8.33% Ethacure® 300. The molar ratio of liquid aromatic diamine to total moles of diamine and polyol in the curing agent mixture is 35%. After curing, a plate with a density of 1.16 g / mL exhibited a tensile modulus of 411 MPa (59,600 psi), a tensile strength of 29.0 MPa (4200 psi), and a tensile elongation of 169%.
[0085] The reaction mixture described above was sprayed into an open mold using a two-component collision-type mixed air atomization system. The MDI prepolymer was loaded into an isotank, and at the same time, 73.75 parts (58.26 pounds) of Voranol® 5055HH, 8.34 parts (6.59 pounds) of monoethylene glycol, 1.84 parts (1.461 pounds) of Niax® L5345, and 15.51 parts (12.25 pounds) of Ethacure® 300 were loaded into a polytank in the same proportions as used in the flattening process described above. The flow rates during spraying were 9.10 g / sec on the polyol side and 7.90 g / sec on the isotank side. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pads were cured in a 100°C oven for 15 minutes, then removed from the mold and cured in a 100°C oven for 16 hours. The resulting pads contained both radial and concentric grooves. The manufactured pads exhibited an average density of 0.813 g / mL, a 15-second Shore D hardness of 57, a bulk tensile modulus of 291.0 MPa (42,200 psi), a tensile strength of 17.9 MPa (2,600 psi), and a tensile elongation of 116%.
[0086] Comparative Example 3: Flat Plate and Pad A blend of equal parts by weight of poly(tetramethylene glycol) (PTMEG) 650, PTMEG 1000, and PTMEG 2000 was prepared. In a mixing cup, 34.65 parts (86.63 g, 0.1754 equivalent moles) of this blend was combined with 1 part (2.50 g) of Niax® L5345 surfactant and 18.24 parts (45.60 g, 0.4262 equivalent moles) of Ethacure® 300. 46.11 parts (115.27 g, 0.6334 equivalent moles) of MDI prepolymer were added to this degassed mixture. The cup was then mixed in a vortex mixer for 20 seconds, and then poured into a mold to form a plate, which was cured at 100°C for 16 hours. The formulation is described as having a weight fraction of 65% hard segments, a stoichiometric ratio of 95%, and containing 18.24% by weight of Ethacure® 300. The molar ratio of liquid aromatic diamine / total moles of diamine and polyol in the curing agent mixture is 100%. After curing, a plate with a density of 1.16 g / mL exhibited a Shore D hardness of 71 at 15 seconds, a tensile modulus of 554.3 MPa (80,400 psi), a tensile strength of 46.88 MPa (6,800 psi), and a tensile elongation of 220%.
[0087] The reaction mixture was sprayed onto an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into an iso-tank, and simultaneously, 20.457 parts (12.60 lbs) of PTMEG650, 20.457 parts (12.60 lbs) of PTMEG1000, 20.457 parts (12.60 lbs) of PTMEG2000, 1.548 parts (0.954 lbs) of Niax L5345, and 36.616 parts (22.55 lbs) of Ethacure300 were loaded into poly-tanks in the same proportions as used in the flat plate processing described above. The flow rates during spraying were 9.59 g / sec on the polyol side and 7.41 g / sec on the iso-tank. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was then guided into a mold with a grooved shape. The sprayed pads were cured in a 100°C oven for 16 hours. The resulting pads contained both radial and concentric grooves. The resulting pads exhibited an average density of 0.791 g / mL, a 15-second Shore D hardness of 56, a bulk tensile modulus of 277 MPa (40,200 psi), a tensile strength of 17.9 MPa (2,600 psi), and a tensile elongation of 112%.
[0088] Comparative Example 4: Flat Plate and Pad A blend of equal parts by weight of poly(tetramethylene glycol) (PTMEG) 650, PTMEG 1000, and PTMEG 2000 was prepared. In a mixing cup, 34.65 parts (86.63 g, 0.1754 equivalent moles) of this blend was combined with 1 part (2.50 g) of Niax® L5345 surfactant, 10.45 parts (26.128 g, 0.2442 equivalent moles) of Ethacure® 300, and 3.02 parts (7.57 g, 0.2442 equivalent moles) of monoethylene glycol. 50.87 parts (127.18 g, 0.6988 equivalent moles) of MDI prepolymer was added to this degassed mixture. The cup was then mixed in a vortex mixer for 20 seconds, then poured into a mold to form a plate, and cured at 100°C for 16 hours. The formulation is described as having a weight fraction of 65% hard segments, a stoichiometric ratio of 95%, and containing 10.45% by weight of Ethacure® 300. The molar ratio of liquid aromatic diamine / total moles of diamine and polyol in the curing agent mixture is 50%. After curing, a plate with a density of 1.16 g / mL exhibited a Shore D hardness of 67 at 15 seconds, a tensile modulus of 467.5 MPa (67,800 psi), a tensile strength of 40.0 MPa (5,800 psi), and a tensile elongation of 230%.
[0089] The reaction mixture described above was sprayed onto an open mold using a two-component collision-type mixed air atomization system. The MDI prepolymer was loaded into the iso tank, and at the same time, 22.62 parts (16.92 pounds) of PTMEG650, 22.62 parts (16.92 pounds) of PTMEG1000, 22.62 parts (16.92 pounds) of PTMEG2000, 1.712 parts (1.281 pounds) of Niax® L5345, 6.72 parts (5.025 pounds) of monoethylene glycol, and 23.195 parts (17.35 pounds) of Ethacure® 300 were loaded into the poly tank in the same proportions as used in the flattening process described above. The flow rates during spraying were 8.67 g / sec on the polyol side and 8.33 g / sec on the iso side. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.848 g / mL, a 15-second Shore D hardness of 58, a bulk tensile modulus of 324.0 MPa (47,000 psi), a tensile strength of 19.3 MPa (2,800 psi), and a tensile elongation of 197%.
[0090] Example 5: Flat plate and pad A blend of equal parts by weight of poly(tetramethylene glycol) (PTMEG) 650, PTMEG 1000, and PTMEG 2000 was prepared. In a mixing cup, 34.65 parts (86.63 g, 0.1754 equivalent mol) of this blend was combined with 1 part (2.50 g) of Niax® L5345 surfactant, 7.65 parts (19.13 g, 0.179 equivalent mol) of Ethacure® 300, and 4.11 parts (10.29 g, 0.332 equivalent mol) of monoethylene glycol. 52.58 parts (131.46 g, 0.722 equivalent mol) of MDI prepolymer was added to this degassed mixture. The cup was then mixed in a vortex mixer for 20 seconds, then poured into a mold to form a plate, and cured at 100°C for 16 hours. The formulation is described as having a weight fraction of 65% hard segments, a stoichiometric ratio of 95%, and containing 7.65% by weight of Ethacure® 300. The molar ratio of liquid aromatic diamine to total moles of diamine and polyol in the curing agent mixture is 35%. After curing, a plate with a density of 1.16 g / mL exhibited a Shore D hardness of 66 at 15 seconds, a tensile modulus of 411.6 MPa (59,700 psi), a tensile strength of 39.3 MPa (5,700 psi), and a tensile elongation of 290%.
[0091] The reaction mixture was sprayed onto an open mold using a two-component collision air spray system. The MDI prepolymer was loaded into an isotank, and at the same time, 24.22 parts (13.92 lbs) of PTMEG650, 24.22 parts (13.92 lbs) of PTMEG1000, 24.22 parts (13.92 lbs) of PTMEG2000, 2.10 parts (1.20 lbs) of Niax® L5345, 8.63 parts (4.96 lbs) of monoethylene glycol, 16.05 parts (9.225 lbs) of Ethacure® 300, 0.43 parts (0.246 lbs) of DABCO® 33-LV catalyst, and 0.142 parts (0.082 lbs) of bismuth neodecanoate catalyst were loaded into polytanks in the same proportions as used in the plaque work described above. The flow rates during spraying were 8.98 g / sec on the polyol side and 10.02 g / sec on the iso side. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in a 100°C oven for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.650 g / mL, a 15-second Shore D hardness of 47.6, a bulk tensile modulus of 226.8 MPa (32,900 psi), a tensile strength of 18.6 MPa (2,700 psi), and a tensile elongation of 190%.
[0092] Example 6: Pad The reaction mixture was sprayed into an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into an isotank, and at the same time, 25.13 parts (17.97 lbs) of PTMEG650, 25.13 parts (17.97 lbs) of PTMEG1000, 25.13 parts (17.97 lbs) of PTMEG2000, 1.90 parts (1.36 lbs) of Niax® L5345, 4.988 parts (3.57 lbs) of monoethylene glycol, 17.21 parts (12.31 lbs) of Ethacure® 300, 0.381 parts (0.273 lbs) of DABCO® 33-LV catalyst, and 0.127 parts (0.091 lbs) of bismuth neodecanoate catalyst were loaded into polytanks. The flow rates during spraying were 9.90 g / sec on the polyol side and 9.10 g / sec on the iso side. The formulation is described as having a weight fraction of 60% hard segments, a stoichiometric ratio of 95%, and containing 9.02 wt% Ethacure® 300. The molar ratio of liquid aromatic diamine to the total number of moles of diamine and polyol in the curing agent mixture is 50%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane formulation was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The resulting pads exhibited an average density of 0.704 g / mL, a Shore D hardness of 40 for 15 seconds, a bulk tensile modulus of 137.2 MPa (19,900 psi), a tensile strength of 17.9 MPa (2,600 psi), and a tensile elongation of 260%.
[0093] Example 7: Pad The reaction mixture was sprayed into an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into an isotank, and at the same time, 26.13 parts (21.20 lbs) of PTMEG650, 26.13 parts (21.20 lbs) of PTMEG1000, 26.13 parts (21.20 lbs) of PTMEG2000, 1.98 parts (1.60 lbs) of Niax® L5345, 7.70 parts (6.25 lbs) of monoethylene glycol, 11.40 parts (9.25 lbs) of Ethacure® 300, 0.397 parts (0.322 lbs) of DABCO® 33-LV catalyst, and 0.132 parts (0.107 lbs) of bismuth neodecanoate catalyst were loaded into polytanks. The flow rates during spraying were 9.52 g / sec on the polyol side and 9.48 g / sec on the iso side. The formulation is described as having a weight fraction of 60% hard segments, a stoichiometric ratio of 95%, and containing 5.75 wt% Ethacure® 300. The molar ratio of liquid aromatic diamine to the total number of moles of diamine and polyol in the curing agent mixture is 30%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane formulation was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The resulting pads exhibited an average density of 0.711 g / mL, a 15-second Shore D hardness of 39, a bulk tensile modulus of 117.9 MPa (17,100 psi), a tensile strength of 16.5 MPa (2,400 psi), and a tensile elongation of 260%.
[0094] Comparative Example 8: Pad The reaction mixture was sprayed into an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into an isotank, while simultaneously loading 87.99 parts (61.593 pounds) of PolyTHF650, 0.88 parts (0.616 pounds) of Niax® L5345 nonionic surfactant, 0.088 parts (0.062 pounds) of Niax® T-9 catalyst, 0.2642 parts (0.185 pounds) of DABCO® 33LV, 0.22 parts (0.154 pounds) of water, and 10.557 parts (7.39 pounds) of dipropylene glycol into a polytank. The flow rates during spraying were 9.10 g / sec on the polyol side and 9.90 g / sec on the iso side. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided onto a Teflon® coated aluminum plate. The sprayed pads were cured in a 100°C oven for 16 hours. The resulting pads were described as having a 52.5% hard segment weight fraction by 95% stoichiometry. With the addition of 2500 ppm of water, a pad with a bulk density of 0.53 g / mL was produced, exhibiting a bulk tensile modulus of 1.2 MPa (170 psi), a tensile strength of 6.0 MPa (870 psi), and a tensile elongation of 535%, with a 15-second Shore A hardness of 27.
[0095] Comparative Example 9: A commercially available IC1000 polishing pad (Dow) having the same K7R32 groove pattern and the same SUBA(trademark) IV sub-pad (Dow) as used in other polishing experiments. The density was 0.77 g / mL and the tensile modulus was 260 MPa (37,700 psi).
[0096] Example 10: Pad The reaction mixture was sprayed into an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into the iso-tank, while simultaneously, 84.85 parts of PTMEG1000, 3.48 parts of INT1940, 0.24 parts of AOX1, 4.46 parts of monoethylene glycol, 6.59 parts of Ethacure® 300, and 0.38 parts of bismuth octo-art catalyst were loaded into the poly-tank. The spray flow rates were 4.6 g / sec on the polyol side and 3.4 g / sec on the iso-tank side. The formulation is described as having a 50% hard segment weight fraction, a 95% stoichiometric ratio, and containing 3.79% by weight of Ethacure® 300. The molar ratio of liquid aromatic diamine to total moles of diamine and polyol in the curing agent mixture is 30%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.68 g / mL, a 15-second hardness Shore DO of 32, a bulk tensile modulus of 4 MPa (600 psi), a tensile strength of 11 MPa (1500 psi), and a tensile elongation of 550%.
[0097] Example 11: Pad The reaction mixture was sprayed into an open mold using a two-component collision-type mixed air atomization system. The MDI prepolymer was loaded into the iso-tank, while simultaneously, 81.96 parts of PTMEG1000, 3.65 parts of INT1940, 0.26 parts of AOX1, 5.54 parts of monoethylene glycol, 8.2 parts of Ethacure® 300, and 0.4 parts of bismuth octo-art catalyst were loaded into the poly-tank. The spray flow rates were 4.6 g / sec on the polyol side and 3.8 g / sec on the iso-tank side. The formulation is described as having a hard segment weight fraction of 54%, a stoichiometric ratio of 95%, and containing 4.49 wt% of Ethacure® 300. The molar ratio of liquid aromatic diamine to total moles of diamine and polyol in the curing agent mixture is 30%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.70 g / mL, a 15-second Shore DO of 49, a bulk tensile modulus of 12 MPa (1700 psi), a tensile strength of 15 MPa (2100 psi), and a tensile elongation of 500%.
[0098] Example 12: Pad The reaction mixture was sprayed into an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into the iso-tank, while simultaneously, 79.8 parts of PTMEG1000, 3.55 parts of INT1940, 0.25 parts of AOX1, 6.46 parts of monoethylene glycol, 9.55 parts of Ethacure® 300, and 0.39 parts of bismuth octo-art catalyst were loaded into the poly-tank. The spray flow rates were 4.6 g / sec on the polyol side and 3.6 g / sec on the iso-tank. The formulation is described as having a hard segment weight fraction of 54%, a stoichiometric ratio of 110%, and containing 5.38 wt% of Ethacure® 300. The molar ratio of liquid aromatic diamine to total moles of diamine and polyol in the curing agent mixture is 30%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.73 g / mL, a 15-second hardness Shore DO of 43, a bulk tensile modulus of 8 MPa (1200 psi), a tensile strength of 8 MPa (1200 psi), and a tensile elongation of 530%.
[0099] Example 13: Pad The reaction mixture was sprayed into an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into the iso-tank, while simultaneously, 77.32 parts of PTMEG1000, 3.68 parts of INT1940, 0.26 parts of AOX1, 7.39 parts of monoethylene glycol, 10.94 parts of Ethacure® 300, and 0.41 parts of bismuth octo-art catalyst were loaded into the poly-tank. The spray flow rates were 4.6 g / sec on the polyol side and 3.9 g / sec on the iso-tank. The formulation is described as having a hard segment weight fraction of 57%, a stoichiometric ratio of 110%, and containing 5.94 wt% of Ethacure® 300. The molar ratio of liquid aromatic diamine to total moles of diamine and polyol in the curing agent mixture is 30%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.74 g / mL, a 15-second hardness Shore DO of 56, a bulk tensile modulus of 21 MPa (3100 psi), a tensile strength of 3 MPa (500 psi), and a tensile elongation of 85%.
[0100] Example 14: Pad The reaction mixture was sprayed into an open mold using a two-component collision-type mixed air atomization system. The MDI prepolymer was loaded into the iso tank, and simultaneously, 24.6 parts of PTMEG650, 24.6 parts of PTMEG1000, 24.6 parts of PTMEG2000, 1.87 parts of Niax® L5345, 14.23 parts of dipropylene glycol, 9.73 parts of Ethacure® 300, and 0.37 parts of bismuth neodecanoate catalyst were loaded into the poly tank. The flow rates during spraying were 10.4 g / sec on the polyol side and 9.1 g / sec on the iso side. The formulation is described as having a weight fraction of 60% hard segments, a stoichiometric ratio of 95%, and containing 5.21% by weight of Ethacure® 300. The molar ratio of liquid aromatic diamine / total moles of diamine and polyol in the curing agent mixture is 30%. The air injected into the nozzle was set to a nominal velocity of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.45 g / mL, a Shore D hardness of 14 for 15 seconds, a bulk tensile modulus of 27 MPa (3900 psi), a tensile strength of 7 MPa (1100 psi), and a tensile elongation of 300%.
[0101] Example 15: Pad The reaction mixture was sprayed into an open mold using a two-component collision-type mixed air spray system. The MDI prepolymer was loaded into an iso-tank, and simultaneously, 25.49 parts of PTMEG650, 25.49 parts of PTMEG1000, 25.49 parts of PTMEG2000, 1.94 parts of Niax® L5345, 10.51 parts of 1,4-butanediol, 10.7 parts of Ethacure® 300, and 0.39 parts of bismuth neodecanoate catalyst were loaded into a poly-tank. The spray flow rates were 10.1 g / sec on the polyol side and 9.4 g / sec on the iso-tank side. The formulation is described as having a 60% hard segment weight fraction, a 95% stoichiometric ratio, and containing 5.53% by weight of Ethacure® 300. The molar ratio of liquid aromatic diamine to the total number of moles of diamine and polyol in the curing agent mixture was 30%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.66 g / mL, a Shore D hardness of 29 at 15 seconds, a bulk tensile modulus of 64 MPa (9300 psi), a tensile strength of 13 MPa (1900 psi), and a tensile elongation of 260%.
[0102] Example 16: Pad The reaction mixture was sprayed into an open mold using a two-component impact air atomization system. The MDI prepolymer was loaded into the isotank, while simultaneously loading 80.26 parts PTMEG1000, 1.91 parts Niax® L5345, 8.01 parts propylene glycol, 9.54 parts Ethacure® 300, and 0.28 parts bismuth neodecanoate catalyst into the polytank. The spray flow rates were 11.1 g / sec on the polyol side and 9.9 g / sec on the isotank side. The formulation is described as having a hard segment weight fraction of 57%, a stoichiometric ratio of 95%, and containing 5.05 wt% Ethacure® 300. The molar ratio of liquid aromatic diamine to total moles of diamine and polyol in the curing agent mixture is 30%. The air injected into the nozzle was set to a nominal rate of 100 L / min. The sprayed polyurethane compound was guided into a mold having a grooved shape. The sprayed pad was cured in an oven at 100°C for 16 hours. The resulting pad contained both radial and concentric grooves. The manufactured pad exhibited an average density of 0.69 g / mL, a 15-second Shore D hardness of 36, a bulk tensile modulus of 81 MPa (11700 psi), a tensile strength of 16 MPa (2300 psi), and a tensile elongation of 280%.
[0103] The characteristics of the materials and pads used in the above examples are reported in Table 1 below. The pads prepared in the above examples were tested for polishing as described in the following test method, and the results are reported in Tables 1 and 2 below, respectively.
[0104] The CMP polishing pad was manufactured by machining the back side of the polishing layer, as indicated in the above embodiment, to be flat on a lathe, thereby providing a flat polishing pad. The polishing pad was then bonded to the SUBA(trademark) IV sub-pad (Dow) via a pressure-sensitive adhesive. The final laminated pad had a diameter of 0.508 mm (20 inches), and the polishing layer was nominally 2.03 mm (80 mils) thick, and had a groove pattern, in which multiple grooves had a width of 0.508 mm (20 mils), a depth of 0.762 mm (30 mils), and a pitch of 1.78 mm (70 mils), and a concentric groove pattern with 32 radial grooves. Polishing experiments were performed on 200 mm wafers on an Applied Mirra polisher (Applied Materials, Santa Clara, California) using carrier downforces of 0.014, 0.016, 0.021, and 0.026 MPa (2.0, 2.3, 3.0, and 3.8 psi), a slurry flow rate of 200 mL / min, and Klebosol® II1730 colloidal silica slurry (Dow, 16 wt% solids), a table rotation speed of 93 rpm, and a carrier rotation speed of 87 rpm. Polishing pads from Examples 1-9, 14, and 15 were conditioned and textured using a 3M® Diamond Pad Conditioner A 153 L, 4.25 inch diameter (The 3M Company, Minneapolis, Minnesota), with abrasiveness grades of 6-9. The polishing pads of Example 16 were conditioned and textured using Saesol Diamond Pad Conditioner AK 45 (Saesol® AM 02 BSL 8031 C 1). The polishing pads of Examples 10-13 were conditioned and textured using Saesol Diamond Pad Conditioner AD45 (Saesol® AM02 BSL 8031 E7). Each polishing pad was run with conditioner and DI water for 30 minutes using only a typical downforce, e.g., 22.2 N or 31.1 N.The polishing pad was further conditioned in situ to 100% while polishing from 1.7 to 9.2 inches from the center of the pad at 10 sweeps / min with a downforce of 22.2 N. The wafer was cleaned with OnTrack DSS-200 Synergy Post CMP. To further accentuate the shallow scratches, HF etching was performed with an SSEC single wafer etch system, thereby etching 200 Å of TEOS from the wafer. Step height measurements for planarization were performed with a Bruker Dynamic Atomic Force Profiler (Bruker, Billerica, Massachusetts). The substrate was a tetraethoxysilicate (TEOS) wafer substrate. The removal rate was determined by measuring the film thickness before and after polishing in a 3 mm edge exclusion area using a KLA-Tencor FX200™ measurement tool (KLA Tencor, Milpitas, California) with a 49-point spiral scan. The removal rate was calculated in Å / min by the change in thickness at each point over a specified polishing time. The non-uniformity rate (%NUR) was calculated by the percentage standard deviation of the removal rate.
[0105] [Table 1]
[0106] [Table 2]
[0107] As shown in Tables 1 and 2 above, the CMP polishing pad of the present invention shows improved planarization efficiency even when compared to the commercially available CMP polishing pad of Comparative Example 10. At the same time, the removal rate and non-uniformity % were the same as or similar to the values produced by the IC 1000 pad (Dow) of Comparative Example 10. Furthermore, the performance of the CMP polishing pad of the present invention was significantly better than the pad from the liquid aromatic diamine curing agent of Comparative Example 3 and the pad from 70% liquid aromatic diamine in a curing agent mixture like that of Comparative Example 1.
Claims
1. 1. A chemical mechanical (CMP) polishing pad for polishing a substrate selected from at least one of a magnetic substrate, an optical substrate, and a semiconductor substrate, comprising: the CMP polishing pad comprises a polishing layer adapted for polishing the substrate; The polishing layer is polyurethane, The polyurethane is (i) a liquid aromatic isocyanate component comprising one or more aromatic diisocyanates or linear aromatic isocyanate-terminated urethane prepolymers having an unreacted isocyanate (NCO) concentration of 20 to 40 weight percent based on the total solids weight of the liquid aromatic isocyanate component; (ii) A liquid polyol component comprising: a) one or more polymer polyols; b) 12 to 40% by weight based on the total weight of the liquid polyol component; one or more short chain difunctional polyols having 2 to 9 carbon atoms, and a curing agent mixture of a liquid aromatic diamine, which is liquid under ambient conditions; A liquid polyol component comprising: and wherein the product of the reaction mixture comprises the molar ratio of the liquid aromatic diamine to the total number of moles of the short chain difunctional polyol and the liquid aromatic diamine is in the range of 15:85 to 40:60; the reaction mixture comprises 48 to 68 weight percent of a hard segment material based on the total weight of the reaction mixture; Further, the CMP polishing pad, wherein the CMP polishing layer has a hardness in the range of 50 Shore A (15 sec) to 68 Shore D (15 sec) and a density of 0.45 to 0.9 g / mL.
2. 2. The CMP polishing pad of claim 1, wherein the (i) liquid aromatic isocyanate component comprises a linear methylene diphenyl diisocyanate (MDI) prepolymer or MDI.
3. 2. The CMP polishing pad of claim 1, wherein the (ii) liquid polyol component comprises one or more polymer polyols selected from the group consisting of a) polytetramethylene glycol (PTMEG), polypropylene glycol (PPG), hexafunctional polyols, and mixtures thereof.
4. 2. The CMP polishing pad of claim 1, wherein in the b) hardener mixture of the (ii) liquid polyol component, the one or more short-chain difunctional polyols having 2 to 9 carbon atoms are selected from the group consisting of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol, and mixtures thereof.
5. 2. The CMP polishing pad of claim 1, wherein in the b) hardener mixture, the liquid aromatic diamine is selected from the group consisting of dimethylthio-toluenediamine, diethyltoluenediamine, tert-butyltoluenediamine, chlorotoluenediamine, N,N'-dialkylaminodiphenylmethane, and mixtures thereof.
6. 2. The CMP polishing pad of claim 1, wherein the molar ratio of the liquid aromatic diamine to the total moles of the short chain difunctional polyol and the liquid aromatic diamine in the b) curing agent mixture is in the range of 23:77 to 35:
65.
7. 10. The CMP polishing pad of claim 1, wherein the reactive mixture comprises 58-63 wt% hard segment material based on the total weight of the reactive mixture.
8. The CMP polishing pad is 2 CMP polishing pad according to claim 1, which does not contain any trace elements other than those formed by the -amine adduct.
9. 13. A method for producing a chemical mechanical (CMP) polishing pad having a polishing layer adapted for polishing a substrate comprising providing the two-component reaction mixture of claim 1, 2. The process of claim 1 , further comprising the steps of: ii) in a liquid polyol component; c) sufficient water or CO to produce density in the CMP polishing pad or layer; 2 - providing a two-component reaction mixture comprising an amine adduct; mixing the (i) liquid aromatic isocyanate component and the (ii) liquid polyol component; applying said reaction mixture in one component to an open mold surface; curing the reaction mixture at ambient temperature to 130° C. to form a shaped polyurethane reaction product; removing the polyurethane reaction product from the mold; and then final curing at a temperature of 60° C. to 130° C. for a period of 1 minute to 18 hours.
10. 10. The method of claim 9, wherein the mold surface has a male shape that forms a female groove pattern on the top surface of the CMP polishing layer.